Increasing the Effectiveness of Stunting Prevention Programs in Adolescent Girls Through Collaboration of Health Workers, Pharmacists and Midwives in Pandeglang Regency: Peningkatan Efektivitas Program Pencegahan Stunting pada Remaja Putri Melalui Kolaborasi Tenaga Kesehatan Apoteker dan Bidan di Kabupaten Pandeglang - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Ashari, Elva Febri; Chairani, Farahdina; Adini, Syilvi; Perdi, Perdi; Ofsah, Olin Najilah; Udin, Baha; Yulistina, Isti; Ristiani, Yuanisa (Universitas Lancang Kuning, 2025)
Adolescent girls with anemia face increased risks during pregnancy and childbirth and are more likely to give birth to stunted children, perpetuating the cycle of intergenerational malnutrition. This community service program involved 150 adolescent girls divided into two groups: 75 in the control group and 75 in the intervention group. Only the intervention group received education using the CBIA (Cara Belajar Insan Aktif) method. Evaluation included hemoglobin level measurements, knowledge assessments on anemia and stunting, and adherence to iron tablet (TTD) consumption. The intervention group showed significant improvements in knowledge, Hb levels, and compliance compared to the control group. Educational interventions using the CBIA method, supported by health worker collaboration, proved effective in improving awareness and TTD adherence among adolescent girls. This approach is promising as a preventive strategy for anemia and stunting